Pinna-Imitating Microphone Directionality Improves Sound Localization and Discrimination in Bilateral Cochlear Implant Users. Issue 1 (January 2021) - Fischer, Tim; Schmid, Christoph; Kompis, Martin; Mantokoudis, Georgios; Caversaccio, Marco; Wimmer, Wilhelm
Abstract : Objectives: To compare the sound-source localization, discrimination, and tracking performance of bilateral cochlear implant users with omnidirectional (OMNI) and pinna-imitating (PI) microphone directionality modes. Design: Twelve experienced bilateral cochlear implant users participated in the study. Their audio processors were fitted with two different programs featuring either the OMNI or PI mode. Each subject performed static and dynamic sound field spatial hearing tests in the horizontal plane. The static tests consisted of an absolute sound localization test and a minimum audible angle test, which was measured at eight azimuth directions. Dynamic sound tracking ability was evaluated by the subject correctly indicating the direction of a moving stimulus along two circular paths around the subject. Results: PI mode led to statistically significant sound localization and discrimination improvements. For static sound localization, the greatest benefit was a reduction in the number of front-back confusions. The front-back confusion rate was reduced from 47% with OMNI mode to 35% with PI mode ( p = 0.03). The ability to discriminate sound sources straight to the sides (90° and 270° angle) was only possible with PI mode. The averaged minimum audible angle value for the 90° and 270° angle positions decreased from a 75.5° to a 37.7° angle when PI mode was used ( p < 0.001). Furthermore, a non-significant trend towards an improvement in the ability to track moving sound sources was observed for both trajectories tested ( p = 0.34 and p = 0.27). Conclusions: Our results demonstrate that PI mode can lead to improved spatial hearing performance in bilateral cochlear implant users, mainly as a consequence of improved front-back discrimination with PI mode. Abstract : Supplemental Digital Content is available in the text.